The relationship of body mass index, mid-upper arm circumference, and waist circumference with the blood pressure in elderly - indriyani indriyani; Rury Tiara; Noviyanti Noviyanti; Cintiya Aprilia (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Life expectancy is one of the most popular summary measures for a population's general health. Growing Life Expectancy predicts a rise in senior citizens in the coming years. An increase in health issues among the elderly may result from an aging population. Anthropometric measures of nutritional status can reveal nutritional status, which may contribute to the development of cardiovascular risk; however, research on this topic in the elderly is still lacking. This study uses a cross-sectional design and a sample size of 60 elderly people who live in Muhammadiyah University Palembang's development village. Blood pressure and anthropometric measures were taken by researchers. Throughout the course of five minutes, three separate readings of the blood pressure, waist circumference, mid-upper arm circumference, and body mass index (BMI) were obtained. The means of these measurements were then analyzed. Diastole Blood Pressure/DBP was substantially correlated with BMI, WC, and MUAC (P = 0.001; r = 0.407; P = 0.003; r = 0.381 & P = 0.017; r = 0.307, respectively). In conclusion, systolic and diastolic blood pressure in the elderly are positively associated with anthropometric measures of body fatness, particularly BMI.